Nepotistic Corruption Breeding For The Establishment Of A Political Dynasty - Syauket, Amalia (Devotion : Journal of Community Service, 2021)
Simultaneous Pilkada 2020 is still dwelling on the same pattern of problems from the previous Pilkada which actually experienced a significant increase in the journey of regional heads who came from the Political Dynasty. A total of 124 candidates are affiliated with political dynasties. One of them is caused by the double-edged sword of decentralization and regional autonomy. In addition to giving power to the regions in forming their own households, decentralization of regional autonomy triggers the decentralization of corruption that spreads to various regions which then drags the political elite. This is what causes regional autonomy to encourage oligarchic decentralization and the practice of political dynasties. The "little kings" in the regions that were born from regional autonomy finally made the Pilkada a power defense industry that was also correlated with the defense of wealth. This research article uses a qualitative approach with a phenomenological type, prioritizing secondary data, with the 4M writing technique, namely Describing, Analyzing, Concluding and Describing the phenomenon of nepotistic corruption which is the seed of political dynasties to answer the problem of how nepotistic corruption forms a political dynasty. The conclusions drawn from this research, this type of corruption refers to preferential treatment given to children, wives, nieces or close relatives of officials at every level, and every route in the formation of political dynasties in other words nepotistic corruption is the seed in the formation of Political Dynasties. because the family as the main pillar in the formation of a political dynasty.